2011
DOI: 10.2113/gssgfbull.182.2.95
|View full text |Cite
|
Sign up to set email alerts
|

Morphostructural evolution of the Luberon since the Miocene (SE France)

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 20 publications
1
12
0
Order By: Relevance
“…In contrast, high percentages of Abies pollen grains (∼31%) in the middle Tortonian (∼9 Ma) Vaugines site, at the base of the Luberon Massif, show that high topography existed in the source area of this site, which is situated within a syncline filled by Miocene sediments derived from erosion of the Luberon anticline crest . Thus, our data is consistent with structural and topographic development of the Luberon Massif by south-directed thrusting during the time interval 10-6 Ma, as suggested by Clauzon et al (2011). The site of Vaugines is today at 430 m elevation, whereas during the middle Tortonian it was near sea level (Table 2).…”
Section: Evolution Of the Western Flanksupporting
confidence: 90%
“…In contrast, high percentages of Abies pollen grains (∼31%) in the middle Tortonian (∼9 Ma) Vaugines site, at the base of the Luberon Massif, show that high topography existed in the source area of this site, which is situated within a syncline filled by Miocene sediments derived from erosion of the Luberon anticline crest . Thus, our data is consistent with structural and topographic development of the Luberon Massif by south-directed thrusting during the time interval 10-6 Ma, as suggested by Clauzon et al (2011). The site of Vaugines is today at 430 m elevation, whereas during the middle Tortonian it was near sea level (Table 2).…”
Section: Evolution Of the Western Flanksupporting
confidence: 90%
“…Several studies have attributed the fold setting to the Late Cretaceous [ Corroy et al ., ; Leleu , ], and the north‐verging thrust to the Eocene [ Bertrand , ; Haug , ; Guieu , ; Tempier , ]. Some studies have indicated south‐verging thrust reactivation (i.e., Luberon, Costes, and Eguilles) that was related to the Alpine deformation spread [ Clauzon , ; Villegier and Andrieux , ; Blès and Gros , ; Clauzon et al ., ; Molliex et al ., ].…”
Section: Discussionmentioning
confidence: 99%
“…The square indicates the location of the Petit Luberon. (b) Geological section S1 through the Grand Luberon mountain (modified from Clauzon et al., )…”
Section: Geological and Geomorphological Settingmentioning
confidence: 99%
“…In the Luberon range, Clauzon et al. () recognised the imprint of two Miocene tectonic phases. In the early Miocene, a first phase induced additional shortening across the Eocene anticline of the Petit Luberon (Langhien, c .…”
Section: Geological and Geomorphological Settingmentioning
confidence: 99%